Connaissances stratigraphiques sur la base du Mésozoique portugais - Palain, C. (2008)
In Portugal, the Mesozoic lower part is principally composed of conglomeratic, arenitic and pelitic deposits, which are here and there associated with carbonates rocks and evaporites. The Germanic Triassic succession is not observed. The Muschelkalk facies do not exist. Carbonates formation, and some thick evaporites deposits (Keuper facies) are of early Jurassic in age. The thick red beds accumulations deposited in a continental environment are Triassic. In Coimbra area the oldest palynomorphs found are Camian-Norian. In South Portugal (Algarve), the triassic serie must be more complete with a lower Triassic rich in Stegocephales bone-beds.